Caribou exclusion during a population low increases deciduous and evergreen shrub species biomass and nitrogen pools in low Arctic tundra. (24th April 2013) - Zamin, Tara J.; Grogan, Paul; Brooker, Rob
Summary Increased shrub growth has been observed across the Arctic with recent climate warming trends, whilst many populations of caribou and reindeer (Rangifer) have been in decline. Paradoxically, our current understanding of the impacts of caribou and reindeer in altering trajectories of Arctic vegetation change is almost entirely dependent on studies with relatively high density semi‐domesticated herds in Fennoscandia. With many wild herd populations across the Arctic presently at much lower densities, it is important to understand the impact of low intensity browsing on shrub biomass and the soil nutrient pools that fuel it. We used exclosures that have been in place for 5 years in mesic birch hummock tundra in the central Canadian low Arctic to investigate the impact of caribou exclusion on tundra shrub biomass, tissue chemistry and plant and soil nitrogen (N) pools. Over the study period, the migratory tundra caribou herd in the region declined from 25% to 7% of its previous population maximum. Caribou exclusion significantly enhanced the above‐ground biomass components of one deciduous shrub (Betula glandulosa) and two evergreen shrubs (Vaccinium vitis‐idaea and Rhododendron subarcticum). In particular, exclusion doubled B. glandulosa leaf biomass and increased V. vitis‐idaea old leaf biomass 1.7 times, with the strongest effects in evergreens present in tissues > 1 year old, indicating a legacy of browsing from the earlier years of the experiment when the caribou population was higher. Meanwhile, Vaccinium uliginosum biomass and overall vascular plant diversity tended to decline with exclusion. Caribou exclusion increased B. glandulosa leaf N pools by 0.15 g N m−2 (equivalent to 12% of the total vascular plant community annual N requirement for apical growth). Altogether exclusion did not alter total above‐ground N pools, but rather led to a redistribution of shoot biomass and N, enhancing spatial variability in a key growth‐limiting resource for tundra plants. Synthesis. Excluding caribou during a population low resulted in ecologically significant changes in the distribution of plant above‐ground biomass and nitrogen, further increasing the dominance of the three most abundant shrubs. These findings demonstrate that, despite uncertainty in herd recovery, Rangifer browsing impacts to both deciduous and evergreen shrub species should be considered for more robust projections of Arctic vegetation change.